REFLECTIONS ON CERTAIN CONDITIONS FOR SUCCESSFULLY CONDUCTING SOME EXPERIMENTS IN CHEMISTRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Consequently, attention is paid to the tasks that must be performed from the bottom of the education system to the training of scientific personnel.